The Rise of Smaller Cities and Its Meaning in International Tourism to Japan - Kitada, Koji (Quaestiones Geographicae, 2011)
The number of foreign tourists visiting Japan has steadily increased in the recent decades. The country has much variety between districts in spite of its small area, and there is a close relation between the variety of tourist resources and preferences of foreign visitors according to their nationalities. For example, prefectures located in the Hokuriku and Hida district, which do not have large cities, have shown a rapid increase in foreign visitors in the recent years and become one of the major international tourist areas in Japan. The district is mainly supported by visitors from Taiwan and Europe seeking tradition of Japan in smaller cities and the beauty of nature. It is true that 75% of foreign tourists visiting Japan come from Asia and many of them prefer shopping in large cities. But it is also important to enhance historic and cultural value of tourist resources to heighten the attraction of Japan: variety between districts.